قيم العمل و علاقتها بالاتزام التنظيمي لدى عمال مؤسسسة سونلغاز بالاغواط - توهامي مسعودة; بن يحي أسماء; صافي محمد (My University, 2023)
This study aims to reveal the relationship between work values and organizational commitment and determine their nature, in addition to determining the levels of workers' perception of work values as well as the level of organizational commitment prevailing in the sample in addition to knowing the significance of differences in work values and organizational commitment according to gender and social status variables. The researchers relied in this study on the descriptive correlational approach, so that the study sample reached (30) individuals from high tires, frames, controllers and implementers, working in Sonelgaz in Laghouat, and they were randomly selected, and ( the organizational commitment scale of Nour Al-Huda 2017), and (the scale of work values of Abdullah bin Ahmed Muhammad Al-Attas 2009), and these data were also analyzed using the statistical packages program for the social sciences (SPSS) version No. (22), so the results of the study were as follows: 1- There is a statistically significant relationship between work values and organizational commitment among Sonelgaz workers in Laghouat. 2- There are no statistically significant differences in the degrees of work values and organizational commitment among the workers of Sonelgaz in Laghouat by sex. 3- There are no statistically significant differences in the degrees of work values and organizational commitment among the workers of Sonelgaz in Laghouat according to social status. Keywords : - Organizational Compliance – Business Values